Recurrence Rate after Endoscopic vs. Open Approaches for Juvenile Nasopharyngeal Angiofibroma: A Meta-analysis - Reyes, Camilo; Bentley, Heather; Gelves, J. Alejandro; Solares, C. Arturo; Byrd, J. Kenneth (Journal of Neurological Surgery Part B: Skull Base, 2019)
Context The effect on recurrence rate between patients with juvenile nasopharyngeal angiofibroma (JNA), treated by an endoscopic versus open approach, has not been well established.Objective A meta-analysis of the available literature concerning recurrence rate in patients who underwent surgery for JNA.Methods A retrospective meta-analysis of studies analyzing recurrence rate after endoscopic or open surgery for patients with JNA was performed using the DerSimonian–Laird random-effects method. English and non-English articles were reviewed using Embase, Medline, and Cochrane databases.Results Among nine studies, including 362 patients from 1981 to 2015, with a mean follow-up of 49.4 months, a total of 89 patients (24.5%) had recurrence. Our analysis revealed a total effect size of −0.16 in favor of endoscopic approach (−0.25 to −0.06, CI [confidence interval] 95%). When analyzing tumor by stage (Radkowski's IA–IIIB n = 299), the endoscopic approach proved to be superior independent of tumor stage (2 vs. 17% for tumors stage IA–IIA, and 26 vs. 32% for tumor stage IIB–IIIB for endoscopic and open approaches respectively; p < 0.05). The endoscopic approach has a statistical significant lower recurrence rate in patients without intracranial compromise when compared with the open approach (13 vs. 28%; p < 0.02). No statistical difference was seen in patients with intracranial compromise (p = 0.5)Conclusion The use of an endoscopic approach to treat JNA has a significantly lower recurrence rate when compared with open approaches. Independent of disease stage, an endoscopic approach should be the standard of care to surgically treat JNA. For cases with intracranial compromise, either approach can be used for surgical resection.
Keywords: juvenile nasopharyngeal angiofibroma; skull base neoplasm; endoscopic anterior skull base resection; craniofacial approach to the skull base; endoscopic endonasal surgery; neoplasm recurrence; treatment outcome